2017
DOI: 10.1515/hukin-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Stress and Coping in Table Tennis

Abstract: The aim of this study was to examine the relationship between cognitive competitive anxiety intensity and coping strategies in table tennis players. One hundred and two (102) US competitive table tennis players of age range from 10 to 60 filled out a Revised Competitive State Anxiety Inventory-2 (CSAI-2R, Cox et al., 2003) at least 30 minutes before the start of their tournament match and a Modified Cope questionnaire (MCOPE; Crocker and Graham, 1995) 15 minutes after they finished their match. Our study found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 18 publications
1
28
0
3
Order By: Relevance
“…In contrast, emotional-based coping, or avoidant coping is the product of believing in uncontrollable stressors and compulsion to endure stressful events. 23,24 We also found that people with higher educational levels and those who performed physical exercise tended to use problem-based coping instead of other forms of coping strategies. These findings support the findings of previous researches.…”
Section: Discussionmentioning
confidence: 64%
“…In contrast, emotional-based coping, or avoidant coping is the product of believing in uncontrollable stressors and compulsion to endure stressful events. 23,24 We also found that people with higher educational levels and those who performed physical exercise tended to use problem-based coping instead of other forms of coping strategies. These findings support the findings of previous researches.…”
Section: Discussionmentioning
confidence: 64%
“…increased confidence and momentum) in table tennis. In this respect, Kurimay, Pope-Rhodius, and Kondric (2017) found that players use avoidance coping (e.g. behavioural disengagement) and emotional-focused coping (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…self-confidence management techniques such as positive self-talk, slow-paced breathing or visualization in order to support and assist the players during phases of increased pressure and anxiety (i.e. such as the 6th and 7th set or after an opponent's comeback in the score) (Kurimay et al, 2017). Moreover, technical-tactical training interventions should take the above mentioned suggestions into account when preparing for competition.…”
Section: Men's Playersmentioning
confidence: 99%
“…Our findings enhance theoretical understanding of anxiety perceived as debilitative by elite table tennis players in some critical situations. These players were unable to deploy effective psychological skills to combat their emotional experiences ( Jones, 1995 ; Biddle and Ntoumanis, 2000 ). Therefore, elite players’ debilitative anxiety was related to their inability to effectively regulate these negative emotions.…”
Section: Discussionmentioning
confidence: 99%